Hydroxyapatite modified drug-loaded slow-release nanofiber and preparation method thereof

By loading drugs in nanofibers and utilizing the porous structure and spindle-like structure of hydroxyapatite, the problems of single sustained release cycle and low utilization of hydrophilic drugs are solved, and the stable and safe sustained release of drugs are achieved.

CN120078702APending Publication Date: 2025-06-03SHAOYANG UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510242194.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2025-02-20
Filing Date
2025-03-03
Publication Date
2025-06-03

AI Technical Summary

Technical Problem

In the prior art, the sustained release cycle of hydrophilic drugs is single, the drug utilization rate is low, and common tablets need to be given frequently, which can easily lead to gastrointestinal side effects and missed administration problems.

Method used

Hydroxyapatite modified drug-loaded sustained-release nanofibers are used to load the drug on porous hydroxyapatite through electrospinning technology and wrapped inside the nanofibers. A variety of sustained-release pathways are provided using spindle-like structures and porous structures.

Benefits of technology

Various sustained-release paths of drugs have been realized, extending the sustained-release time of drugs, improving the utilization rate of drugs, reducing the number of doses, reducing the toxic side effects of drugs, and enhancing the stability and safety of drugs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120078702A_ABST
    Figure CN120078702A_ABST
Patent Text Reader

Abstract

The invention discloses a hydroxyapatite modified drug-loaded slow-release nanofiber and a preparation method thereof, the hydroxyapatite modified drug-loaded slow-release nanofiber has a fusiform structure, the fusiform structure is formed by a skeleton formed by wrapping porous hydroxyapatite in a porous nanofiber, and the skeleton is loaded with a hydrophilic drug; the porous nanofiber comprises a hydrophilic high polymer material and a hydrophobic high polymer material. Meanwhile, hydroxyapatite capable of adsorbing hydrophilic drugs is selected as a drug carrier, then electrostatic spinning is conducted on the drug carrier, the advantages of hydroxyapatite and hydroxyapatite are fully exerted through combination of hydroxyapatite and hydroxyapatite, and the sustained-release preparation prepared through the method can effectively improve the sustained-release effect and the accumulative utilization rate of the drugs in the human body.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of preparation of nanomaterials, and relates to a hydroxyapatite-modified drug-loaded sustained-release nanofiber and a preparation method thereof. Background Art

[0002] Hydroxyapatite has certain biocompatibility, bioactivity, osteoconductivity and adsorption properties, and can receive high attention from scientific research workers in the biomedical field. The above properties contribute to its extremely wide application scenarios. Hydroxyapatite is widely used in many materials in the medical field, such as materials for plastic surgery and oral health in daily use, materials for controlling drug sustained release and for repairing and replacing bone tissue in pharmacy and medicine, and materials for separating and purifying bioactive substances.

[0003] Diclofenac sodium (DS) is a kind of drug that blocks the synthesis of prostaglandins by inhibiting cyclooxygenase, and then produces analgesic, anti-inflammatory and antipyretic effects. Since ordinary tablets of diclofenac sodium need to be taken 2 - 3 times a day, serious gastrointestinal side effects may occur when the dose is too large. If the dose is reduced and taken in small amounts multiple times, problems such as missed doses and poor compliance are likely to occur. A sustained-release preparation refers to a preparation that slowly and non-constantly releases a drug in a specified release medium through a certain specific method, so as to prolong the drug action time, reduce the number of drug administrations, and reduce the toxic and side effects of the drug. Therefore, preparing the drug into a sustained-release preparation can not only reduce the number of drug administrations, but also avoid the phenomenon of sudden drug release, balance the blood drug concentration, reduce the toxic and side effects, and increase the stability of drug treatment.

[0004] Electrospinning is to make the solution electrostatically atomized to obtain ultrafine nanofibers at the nanometer level under the action of a high-voltage electric field. The prepared nanofibers have advantages such as high porosity and large specific surface area, and can be used as one of the methods for preparing new drug dosage forms. If the advantages of electrospinning technology and hydroxyapatite can be combined, it can provide new ideas for solving problems in the sustained-release drug delivery system. Summary of the Invention

[0005] Aiming at the problems of a single sustained-release period and low drug utilization rate of hydrophilic drugs in the prior art, the first object of the present invention is to provide a hydroxyapatite-modified drug-loaded sustained-release nanofiber, which superimposes the sustained-release performance of the nanofiber itself and the sustained-release performance of hydroxyapatite to improve the drug utilization rate; at the same time, the porous structures of hydroxyapatite and nanofiber cooperate with a special spindle-like structure to provide multiple sustained-release pathways for the drug.

[0006] The second object of the present invention is to provide a method for preparing hydroxyapatite-modified drug-loaded sustained-release nanofibers. Hydroxyapatite that can adsorb hydrophilic drugs is selected as the drug carrier, and then electrospinning is carried out on it. The two are combined to give full play to the advantages of both. Moreover, the sustained-release preparation prepared by this method can effectively improve the sustained-release effect and cumulative utilization rate of the drug in the human body.

[0007] To achieve the above technical object, the present invention provides a hydroxyapatite-modified drug-loaded sustained-release nanofiber. The fiber has a spindle-like structure. The spindle-like structure is composed of a framework formed by porous hydroxyapatite wrapped inside porous nanofibers, and the framework is loaded with hydrophilic drugs; the porous nanofibers include hydrophilic polymer materials and hydrophobic polymer materials.

[0008] As a preferred scheme, the hydrophilic drug is loaded in the pores and on the surface of hydroxyapatite and inside the nanofibers. And the porous hydroxyapatite is wrapped inside the porous nanofibers.

[0009] As a preferred scheme, the hydrophilic drug includes diclofenac sodium.

[0010] The principle of the nanofibers of the present invention having multiple sustained-release pathways is as follows: First, the water-soluble drugs dispersed inside the nanofibers are rapidly released as the hydrophilic polymer dissolves; then, the drugs loaded on the surface of hydroxyapatite are released through the pore structure of the fibers; finally, as the hydrophilic polymer completely dissolves, the hydroxyapatite inside the nanofibers is exposed to the solution, and the drugs loaded inside the hydroxyapatite are slowly released from the pores of the hydroxyapatite, prolonging the sustained-release time of the drugs; in addition, the spindle-like structure makes the overall structure have different diameters. In the thin part, the internal drug release path is short and the drug is easily released; in the thick part, it takes a longer time for the internal drug to be released, so the drug release time is extended. Since the diameter of the spindle structure has a gradual change, the drug release time also has a gradual change.

[0011] The present invention also provides a method for preparing hydroxyapatite-modified drug-loaded sustained-release nanofibers, including the following steps:

[0012] (1) After mixing calcium chloride, diammonium hydrogen phosphate and urea, then adding nitric acid dropwise until the solution is clear, and then adding L-glutamic acid and stirring for hydrothermal reaction. After natural cooling, centrifuging and washing to obtain the precipitate, and freeze-drying to obtain porous hydroxyapatite;

[0013] (2) Dispersing the porous hydroxyapatite and the hydrophilic drug in water and mixing and stirring until the water is completely volatilized to obtain the drug-loaded hydroxyapatite powder;

[0014] (3) Dissolve the hydrophilic polymer material and the hydrophobic polymer material in dichloromethane, and then mix them with the drug-loaded hydroxyapatite powder to obtain a spinning solution.

[0015] (4) Aspirate the spinning solution for electrospinning and control the spinning temperature at 30 - 40°C. After drying, the product is obtained.

[0016] The technical solution of the present invention utilizes hydroxyapatite to adsorb drugs, enabling the drug-loaded hydroxyapatite to be evenly distributed in the spinning solution containing hydrophobic and hydrophilic polymer materials. Subsequently, a nanofiber structure with uniform distribution of drug-loaded hydroxyapatite is prepared through electrospinning. The formation of the porous structure on the surface of the nanofibers in the present invention is mainly due to the phase separation of the polymer solution system of the present invention within the temperature range of the present invention, and at the same time, the solvent volatilizes to form a porous structure on the fiber surface. The key to achieving the spindle-shaped structure in the present invention lies in controlling the temperature of electrospinning. During the electrospinning process, since the solvent selected in the present invention is dichloromethane, which has strong volatility and a boiling point within the controllable range of electrospinning, the evaporation rate of dichloromethane can be increased by changing the spinning temperature, thereby affecting the occurrence of phase separation. At the same time, when the solvent volatilizes too quickly, the solution has partially solidified before reaching the collector, thus forming a spindle-shaped structure with a diameter that gradually becomes thinner, then thicker, and then thinner.

[0017] The inventors found that when the temperature of electrospinning is too low, it is not conducive to the volatilization of dichloromethane and the spindle-shaped structure cannot be formed; while when the temperature of electrospinning is too high, the structure of hydrophilic drug molecules will be damaged.

[0018] As a preferred solution, in step (1), the conditions of the hydrothermal reaction are: temperature 150 - 250°C, time 8 - 12 h.

[0019] As a preferred solution, in step (2), during the mixing process, the temperature is controlled at 35 - 40°C and ultrasonic is used to promote drug adsorption, and then it is stirred at 80 - 85°C until the water is completely volatilized.

[0020] As a preferred embodiment, the mass ratio of the porous hydroxyapatite to the hydrophilic drug is (0.5 to 5):1. Since the porous hydroxyapatite itself has a certain adsorption capacity, the drug is first adsorbed on the pore structure and outer surface of the hydroxyapatite-loaded carrier and then electrospun to prolong the drug release time. The mass ratio of the porous hydroxyapatite to the hydrophilic drug is the key factor affecting the release performance of the material of the present invention. If the mass ratio of the porous hydroxyapatite to the hydrophilic drug is too low, the hydrophilic drug cannot be completely adsorbed in the porous hydroxyapatite, resulting in most of the drug in the sustained-release nanofibers being wrapped inside the polymer rather than being loaded in the hydroxyapatite, which increases the initial burst release of the nanofibers during the early stage of drug release and causes drug side effects. If the mass ratio of the porous hydroxyapatite to the hydrophilic drug is too high, the drug release amount may not reach the therapeutic dose.

[0021] As a preferred embodiment, the mass ratio of the hydrophobic polymer material to the hydrophilic polymer material is (1 to 5):1. The hydrophilic polymer material has good solubility in the release solution and can release a part of the drug after dissolution. However, if all the nanofibers are composed of hydrophilic polymers, it will cause an initial burst release of the drug and no sustained-release effect can be obtained. The hydrophobic polymer serves as the skeleton and is insoluble in the release solution, which prolongs the drug release time. However, if all the nanofibers are composed of hydrophobic polymers, the drug-loaded porous hydroxyapatite will be completely coated in the nanofibers and is difficult to release, resulting in low drug utilization rate.

[0022] As a preferred embodiment, the mass percentage of the drug-loaded hydroxyapatite in the spinning solution is 0.35 to 4 wt%, and the total mass percentage of the hydrophilic polymer material and the hydrophobic polymer material is 10 to 12 wt%, with the balance being dichloromethane. Within the range of the spinning solution components set in the present invention, while ensuring the integrity of the fiber structure, the release rate of the hydrophilic drug can be comprehensively regulated to enable its stable distribution and controlled release in the body.

[0023] As a preferred embodiment, the hydrophobic polymer material is PLA or PCL; the hydrophilic polymer material is PVA.

[0024] As a preferred embodiment, the spinning conditions are: the needle voltage is 9 to 15 kV, the receiving distance is 12 to 18 cm, and the rotational speed of the receiving roller is 700 to 1200 r / min. Under the spinning conditions selected in the present invention, rapid evaporation of the solvent can be ensured without damaging the structure of the drug molecules.

[0025] As a preferred solution, the propulsion speed of the spinning solution is 0.8 - 1.5 ml / h. At the selected propulsion speed of the spinning solution in the present invention, it can be ensured that during the spinning process, the droplets will not solidify before being fully stretched due to too fast a propulsion speed, resulting in fiber breakage of the spinning solution, nor will the feeding be insufficient due to too slow a propulsion speed, causing the spinning process to interrupt and continuous fibers cannot be formed.

[0026] As a preferred solution, the drying conditions are: the temperature is 40 - 50 °C and the time is 30 - 60 min. After drying, the obtained drug-loaded sustained-release nanofiber membrane is sealed and stored in a dark and dry environment for standby. By spinning the nanofibers into a membrane and performing a sealing treatment, the drug release environment in actual applications can be simulated. The sealed nanofiber membrane can prevent the unexpected release of drugs and ensure the stable distribution of drugs in the body.

[0027] Compared with the prior art, the present invention has the following beneficial effects:

[0028] 1) The present invention adopts the electrospinning technology, which is simple to operate and the parameters are controllable; the selected drug-loading medium and biodegradable polymer materials are easily available and the reaction conditions are mild.

[0029] 2) The present invention uses hydroxyapatite-modified porous nanofibers as drug carriers. First, the drug is loaded on the hydroxyapatite, and then it is wrapped inside the nanofibers by electrospinning; through the superposition of the sustained-release performance of the nanofibers themselves and the sustained-release performance of hydroxyapatite, and at the same time, the porous structures of hydroxyapatite and nanofibers cooperate with the special spindle-shaped structure to provide multiple sustained-release pathways for the drug; avoiding the side effects caused by the sudden release of drugs, reducing the number of drug administrations, facilitating the control of the drug dosage, and improving the safety of drug use.

[0030] 3) The drug-loading polymer selected in the present invention has biodegradability and biocompatibility. It not only provides a certain hydrophobicity to the drug-loading system to ensure the stability of the drug-loading scaffold, but also provides a certain hydrophilicity to ensure the binding of the drug and the polymer, which can effectively improve the absorption and volatilization effects of the drug in the organism and optimize the drug administration method.

[0031] 4) The present invention selects different temperatures for electrospinning, which changes the evaporation rate of the dichloromethane solvent, and then changes the nanofiber structure to obtain nanofibers with a spindle-shaped structure. The nanofibers with a spindle structure are equivalent to nanofibers with different diameters. In the thin part, the internal drug release path is short and the drug is easily released; in the thick part, the internal drug release takes a longer time to release, so the drug release time is extended. Since the diameter of the spindle structure has a gradual change, the drug release time also has a gradual change, which is particularly suitable for hydrophilic sustained-release preparations. Description of the Drawings

[0032] Figure 1 SEM images of the porous nanofibers prepared in Examples 1-4 and Comparative Examples 1-4 (corresponding to Figure 1 (a) - Figure 1 (f)) respectively).

[0033] Figure 2 In vitro release comparison of the drug-loaded nanofibers prepared in Examples 1-4 and Comparative Examples 1-4. Detailed implementation manners

[0034] The present invention will be further described below in conjunction with specific embodiments, but the protection scope of the present invention is not limited to the following specific embodiments. Obviously, the embodiments described below are only a part of the embodiments, and all other embodiments obtained by those skilled in the art without creative efforts still fall within the protection scope of the present invention.

[0035] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in the present invention can be obtained through market purchase or can be prepared by existing methods.

[0036] The porous hydroxyapatite in the examples and comparative examples of the present invention was prepared by the following steps: After mixing 1.5 g of calcium chloride, 0.6 g of diammonium hydrogen phosphate and 4 g of urea, 5 ml of nitric acid was added dropwise until the solution became clear, and then 1.8 g of L-glutamic acid was added and stirred for hydrothermal reaction (temperature: 190 °C, time: 10 h). After natural cooling, centrifugation and washing were carried out to obtain the precipitate, and freeze-drying was performed to obtain the porous hydroxyapatite.

[0037] Example 1

[0038] (1) Preparation of drug-loaded porous hydroxyapatite: Diclofenac sodium drug and the porous hydroxyapatite prepared by the above preparation method were dispersed in water at a mass ratio of 1:1, and ultrasonic dispersion was carried out at 37 °C to adsorb the drug on the porous hydroxyapatite, and then stirring was carried out at 80 °C until the water was completely volatilized, and it was ground to obtain the drug-loaded porous hydroxyapatite powder.

[0039] (2) Preparation of the spinning precursor solution: A hydrophilic polymer (PVA) and a hydrophobic polymer (PLA) were dissolved in dichloromethane, stirred at 37 °C until completely mixed evenly, and then the above-mentioned drug-loaded porous hydroxyapatite powder was added, and stirring was continued until the porous hydroxyapatite powder was evenly dispersed in the polymer solution. The total concentration of PLA and PVA was 12 wt%, the mass ratio was 1:1, and the mass concentration of the drug-loaded porous hydroxyapatite was 4 wt%.

[0040] (3) Preparation of porous drug-loaded nanofibers: Aspirate the above spinning solution into a 10 ml syringe, and select an 18G needle for electrospinning. Fix the syringe to the syringe pump and push it at a speed of 0.85 ml / h. Apply a 15 kV high-voltage electric field between the syringe tip and the receiver, with a receiving distance of 15 cm. At the same time, rotate the receiver at a speed of 800 r / min. After electrospinning is completed at 38 °C, spindle-shaped drug-loaded nanofibers are obtained.

[0041] (4) Sample collection: Place the nanofibers in a constant-temperature oven and dry them at 50 °C for 1 h. Finally, place them in a sealed bag and store them in the dark for future use.

[0042] Example 2

[0043] (1) Preparation of drug-loaded porous hydroxyapatite: Disperse sodium diclofenac drug and the porous hydroxyapatite prepared by the above preparation method in water at a mass ratio of 1:3, and ultrasonically disperse them at 37 °C to adsorb the drug on the porous hydroxyapatite. Then stir at 80 °C until the water is completely evaporated, and grind it to obtain drug-loaded porous hydroxyapatite powder.

[0044] (2) Preparation of spinning precursor solution: Dissolve hydrophilic polymer (PVA) and hydrophobic polymer (PLA) in dichloromethane, stir at 37 °C until they are completely mixed evenly, then add the above drug-loaded porous hydroxyapatite powder, and continue to stir until the porous hydroxyapatite powder is evenly dispersed in the polymer solution. The total concentration of PLA and PVA is 12 wt%, the mass ratio is 1:1, and the mass concentration of drug-loaded porous hydroxyapatite is 4 wt%.

[0045] (3) Preparation of porous drug-loaded nanofibers: Aspirate the above spinning solution into a 10 ml syringe, and select an 18G needle for electrospinning. Fix the syringe to the syringe pump and push it at a speed of 0.85 ml / h. Apply a 15 kV high-voltage electric field between the syringe tip and the receiver, with a receiving distance of 15 cm. At the same time, rotate the receiver at a speed of 800 r / min. After electrospinning is completed at 38 °C, spindle-shaped porous drug-loaded nanofibers are obtained.

[0046] (4) Sample collection: Place the nanofibers in a constant-temperature oven and dry them at 50 °C for 1 h. Finally, place them in a sealed bag and store them in the dark for future use.

[0047] Example 3

[0048] (1) Preparation of drug-loaded porous hydroxyapatite: Disperse sodium diclofenac drug and the porous hydroxyapatite prepared by the above preparation method in water at a mass ratio of 1:4, and ultrasonically disperse them at 37 °C to adsorb the drug on the porous hydroxyapatite. Then stir at 80 °C until the water is completely evaporated, and grind it to obtain drug-loaded porous hydroxyapatite powder.

[0049] (2) Preparation of the spinning precursor solution: Dissolve the hydrophilic polymer (PVA) and the hydrophobic polymer (PLA) in dichloromethane, stir at 37 °C until they are completely and evenly mixed, then add the above-mentioned drug-loaded porous hydroxyapatite powder, and continue to stir until the porous hydroxyapatite powder is evenly dispersed in the polymer solution. The total concentration of PLA and PVA is 12 wt%, the mass ratio is 1:1, and the mass concentration of the drug-loaded porous hydroxyapatite is 4 wt%.

[0050] (3) Preparation of the porous drug-loaded nanofibers: Aspirate the above-mentioned spinning solution into a 10 ml syringe, and use an 18G needle for electrospinning. Fix the syringe to the syringe pump and push it at a speed of 0.85 ml / h. Apply a 15 kV high-voltage electric field between the syringe tip and the receiver, and the receiving distance is 15 cm; at the same time, the receiver rotates at a speed of 800 r / min, and spindle-shaped porous drug-loaded nanofibers are obtained after electrospinning in an environment of 38 °C.

[0051] (4) Sample collection: Place the nanofibers in a constant-temperature oven and dry them at 50 °C for 1 h, and finally place them in a sealed bag and store them in the dark for later use.

[0052] Example 4

[0053] (1) Preparation of the drug-loaded porous hydroxyapatite: Disperse the sodium diclofenac drug and the porous hydroxyapatite prepared by the above preparation method in water at a mass ratio of 1:1, and ultrasonically disperse them at 37 °C to adsorb the drug on the porous hydroxyapatite, and then stir at 85 °C until the water is completely volatilized, and grind it to obtain the drug-loaded porous hydroxyapatite powder.

[0054] (2) Preparation of the spinning precursor solution: Dissolve the hydrophilic polymer (PVA) and the hydrophobic polymer (PLA) in dichloromethane, stir at 37 °C until they are completely and evenly mixed, then add the above-mentioned drug-loaded porous hydroxyapatite powder, and continue to stir until the porous hydroxyapatite powder is evenly dispersed in the polymer solution. The total concentration of PLA and PVA is 10 wt%, the mass ratio is 5:1, and the mass concentration of the drug-loaded porous hydroxyapatite is 2 wt%.

[0055] (3) Preparation of the porous drug-loaded nanofibers: Aspirate the above-mentioned spinning solution into a 10 ml syringe, and use an 18G needle for electrospinning. Fix the syringe to the syringe pump and push it at a speed of 1.5 ml / h. Apply a 9 kV high-voltage electric field between the syringe tip and the receiver, and the receiving distance is 15 cm; at the same time, the receiver rotates at a speed of 800 r / min, and spindle-shaped porous drug-loaded nanofibers are obtained after electrospinning in an environment of 40 °C.

[0056] (4) Sample collection: Place the nanofibers in a constant-temperature oven and dry them at 50 °C for 1 h. Finally, place them in a sealed plastic bag and store them in the dark for future use.

[0057] Comparative Example 1

[0058] The difference between this comparative example and Example 1 is only that the electrospinning temperature is changed to 20 °C, and the remaining steps and conditions are the same, obtaining porous drug-loaded nanofibers.

[0059] (1) Preparation of drug-loaded porous hydroxyapatite: Disperse sodium diclofenac drug and the porous hydroxyapatite prepared by the above preparation method in water at a mass ratio of 1:1, and ultrasonically disperse them at 37 °C to adsorb the drug on the porous hydroxyapatite. Then stir at 80 °C until the water is completely evaporated, and grind it to obtain drug-loaded porous hydroxyapatite powder.

[0060] (2) Preparation of the spinning precursor solution: Dissolve hydrophilic polymer (PVA) and hydrophobic polymer (PLA) in dichloromethane, stir at 37 °C until they are completely mixed evenly, then add the above drug-loaded porous hydroxyapatite powder, and continue to stir until the porous hydroxyapatite powder is evenly dispersed in the polymer solution. The total concentration of PLA and PVA is 12 wt%, the mass ratio is 1:1, and the mass concentration of the drug-loaded porous hydroxyapatite is 4 wt%.

[0061] (3) Preparation of porous drug-loaded nanofibers: Aspirate the above spinning solution into a 10 ml syringe, and select an 18G needle for electrospinning. Fix the syringe on a syringe pump and push it at a speed of 0.85 ml / h. Apply a 15 kV high-voltage electric field between the syringe tip and the receiver, and the receiving distance is 15 cm; at the same time, the receiver rotates at a speed of 800 r / min, and spindle-shaped drug-loaded nanofibers are obtained after electrospinning in a 20 °C environment.

[0062] (4) Sample collection: Place the nanofibers in a constant-temperature oven and dry them at 50 °C for 1 h. Finally, place them in a sealed plastic bag and store them in the dark for future use.

[0063] Comparative Example 2

[0064] The difference between this comparative example and Example 2 is only that the electrospinning temperature is changed to 20 °C, and the remaining steps and conditions are the same, obtaining porous drug-loaded nanofibers.

[0065] (1) Preparation of drug-loaded porous hydroxyapatite: Disperse sodium diclofenac drug and the porous hydroxyapatite prepared by the above preparation method in water at a mass ratio of 1:3, and ultrasonically disperse them at 37 °C to adsorb the drug on the porous hydroxyapatite. Then stir at 80 °C until the water is completely evaporated, and grind it to obtain drug-loaded porous hydroxyapatite powder.

[0066] (2) Preparation of the spinning precursor solution: Dissolve the hydrophilic polymer (PVA) and the hydrophobic polymer (PLA) in dichloromethane, stir at 37 °C until they are completely mixed evenly, then add the above-mentioned drug-loaded porous hydroxyapatite powder, and continue to stir until the porous hydroxyapatite powder is evenly dispersed in the polymer solution. The total concentration of PLA and PVA is 12 wt%, the mass ratio is 1:1, and the mass concentration of the drug-loaded porous hydroxyapatite is 4 wt%.

[0067] (3) Preparation of the porous drug-loaded nanofibers: Draw the above-mentioned spinning solution into a 10 ml syringe, and use an 18G needle for electrospinning. Fix the syringe on the syringe pump and push it at a speed of 0.85 ml / h. Apply a 15 kV high-voltage electric field between the syringe tip and the receiver, and the receiving distance is 15 cm; at the same time, the receiver rotates at a speed of 800 r / min, and the porous drug-loaded nanofibers are obtained after electrospinning in a 20 °C environment.

[0068] (4) Sample collection: Place the nanofibers in a constant-temperature oven and dry them at 50 °C for 1 h, and finally place them in a sealed bag and store them in the dark for later use.

[0069] Comparative Example 3

[0070] The difference between this comparative example and Example 3 is only that the electrospinning temperature is changed to 20 °C, and the other steps and conditions are the same, and the porous drug-loaded nanofibers are obtained.

[0071] (1) Preparation of the drug-loaded porous hydroxyapatite: Disperse the sodium diclofenac drug and the porous hydroxyapatite prepared by the above preparation method in water at a mass ratio of 1:4, and ultrasonicate at 37 °C to adsorb the drug on the porous hydroxyapatite, and then stir at 80 °C until the water is completely evaporated, and grind it to obtain the drug-loaded porous hydroxyapatite powder.

[0072] (2) Preparation of the spinning precursor solution: Dissolve the hydrophilic polymer (PVA) and the hydrophobic polymer (PLA) in dichloromethane, stir at 37 °C until they are completely mixed evenly, then add the above-mentioned drug-loaded porous hydroxyapatite powder, and continue to stir until the porous hydroxyapatite powder is evenly dispersed in the polymer solution. The total concentration of PLA and PVA is 12 wt%, the mass ratio is 1:1, and the mass concentration of the drug-loaded porous hydroxyapatite is 4 wt%.

[0073] (3) Preparation of the porous drug-loaded nanofibers: Draw the above-mentioned spinning solution into a 10 ml syringe, and use an 18G needle for electrospinning. Fix the syringe on the syringe pump and push it at a speed of 0.85 ml / h. Apply a 15 kV high-voltage electric field between the syringe tip and the receiver, and the receiving distance is 15 cm; at the same time, the receiver rotates at a speed of 800 r / min, and the drug-loaded nanofibers are obtained after electrospinning in a 20 °C environment.

[0074] (4) Sample collection: Place the nanofibers in a constant temperature oven and dry them at 50 °C for 1 h. Finally, place them in a sealed plastic bag and store them in the dark for later use.

[0075] Comparative Example 4

[0076] The difference between this comparative example and Example 1 is only that the drug is directly dissolved in the spinning precursor solution without loading the drug on hydroxyapatite. The remaining steps and conditions are the same, and porous spindle-shaped drug-loaded nanofibers are obtained.

[0077] (1) Preparation of the spinning precursor solution: Dissolve the hydrophilic polymer (PVA) and the hydrophobic polymer (PLA) in dichloromethane, stir at 37 °C until they are completely mixed evenly, then add diclofenac sodium and continue to stir until diclofenac sodium is evenly dispersed in the polymer solution. The total concentration of PLA and PVA is 12 wt%, the mass ratio is 1:1, and the mass concentration of diclofenac sodium is 2 wt%.

[0078] (2) Preparation of the porous drug-loaded nanofibers: Aspirate the above spinning solution into a 10 ml syringe and use an 18G needle for electrospinning. Fix the syringe on a syringe pump and push it at a speed of 0.85 ml / h. Apply a 15 kV high-voltage electric field between the syringe tip and the collector, and the receiving distance is 15 cm; at the same time, the collector rotates at a speed of 800 r / min. After electrospinning is completed in an environment of 38 °C, spindle-shaped porous drug-loaded nanofibers are obtained.

[0079] (3) Sample collection: Place the nanofibers in a constant temperature oven and dry them at 50 °C for 1 h. Finally, place them in a sealed plastic bag and store them in the dark for later use.

[0080] The in vitro release experiments of the drug-loaded nanofibers obtained in Examples 1-4 and Comparative Examples 1-4 were carried out as follows: Put a certain volume of the drug-loaded nanofibers into a PBS release medium with pH = 7.2-7.4 and place them in a constant temperature shaker, with the set conditions of 37 °C and 100 r / min. Samples were taken at certain time points, and at the same time, an equal volume of PBS solution at the same temperature was replenished. The in vitro cumulative release amount of the drug was measured with a UV-visible spectrophotometer.

[0081] From Figure 1 (a-f), it can be seen that by comparing the preparation conditions in Examples 1-4 and Comparative Examples 1-4, it is found that when electrospinning is carried out at a certain temperature, nanofibers with a spindle-shaped structure will appear, resulting in a change in the diameter of the nanofibers and a significant decrease in the pore size, indicating that the formation of the nanofiber structure is related to the electrospinning temperature.

[0082] From Figure 2It can be seen that after 250 min, the sustained-release rates of Examples 1 to 4 and Comparative Examples 1 to 4 decreased slowly, and the drug was slowly released. This is because the drug adsorbed in the porous hydroxyapatite was released, extending the drug release time. It can be found by comparison that the sustained-release performance of the nanofibers with spindle-like structures in the examples is better than that of the non-spindle nanofibers in Comparative Examples 1 to 3.

[0083] By comparing Example 1 and Comparative Example 4, it can be found that the sustained-release performance of the hydroxyapatite-loaded drug nanofibers is better than that of the non-hydroxyapatite-loaded drug nanofibers.

Claims

1. A hydroxyapatite-modified drug-loaded sustained-release nanofiber, characterized in that: The invention has a spindle-shaped structure, which is composed of a skeleton composed of porous hydroxyapatite wrapped in porous nanofibers, and the skeleton is loaded with hydrophilic drugs; the porous nanofibers include hydrophilic polymer materials and hydrophobic polymer materials.

2. The hydroxyapatite-modified drug-loaded sustained-release nanofiber according to claim 1, characterized in that: The hydrophilic drug is loaded in the pores and surface of the hydroxyapatite and inside the nanofiber.

3. The method for preparing a hydroxyapatite-modified drug-loaded sustained-release nanofiber according to claim 1 or 2, characterized in that: The following steps are involved: (1) Calcium chloride, diammonium hydrogen phosphate and urea are mixed, nitric acid is added dropwise until the solution is clear, and then L-glutamic acid is added and stirred for hydrothermal reaction. After natural cooling, the precipitate is washed by centrifugation and freeze-dried to obtain porous hydroxyapatite; (2) dispersing porous hydroxyapatite and a hydrophilic drug in water, mixing and stirring until the water is completely volatilized to obtain drug-loaded hydroxyapatite powder; (3) dissolving a hydrophilic polymer material and a hydrophobic polymer material in dichloromethane and mixing the mixture with drug-loaded hydroxyapatite powder to obtain a spinning solution; (4) The spinning solution is absorbed for electrostatic spinning and the spinning temperature is controlled at 30-40° C. The spinning solution is dried to obtain the product.

4. The method for preparing a hydroxyapatite-modified drug-loaded sustained-release nanofiber according to claim 3, characterized in that: In step (2), the temperature is controlled at 35-40° C. during the mixing process, and ultrasound is used to promote drug adsorption, and then the mixture is stirred at 80-85° C. until the water is completely evaporated.

5. The method for preparing a hydroxyapatite-modified drug-loaded sustained-release nanofiber according to claim 4, characterized in that: The mass ratio of the porous hydroxyapatite to the hydrophilic drug is (0.5-5):1; The mass ratio of the hydrophobic polymer material to the hydrophilic polymer material is (1-5):

1.

6. The method for preparing a hydroxyapatite-modified drug-loaded sustained-release nanofiber according to claim 3 or 5, characterized in that: The mass percentage of drug-loaded hydroxyapatite in the spinning solution is 0.35-4wt%, the total mass percentage of hydrophilic polymer material and hydrophobic polymer material is 10-12wt%, and the balance is dichloromethane.

7. The method for preparing a hydroxyapatite-modified drug-loaded sustained-release nanofiber according to claim 6, characterized in that: The hydrophobic polymer material is PLA or PCL; The hydrophilic polymer material is PVA.

8. The method for preparing a hydroxyapatite-modified drug-loaded sustained-release nanofiber according to claim 6, characterized in that: The spinning conditions are as follows: the needle voltage is 9-15 kV, the receiving distance is 12-18 cm, and the receiving roller speed is 700-1200 r / min.

9. The method for preparing a hydroxyapatite-modified drug-loaded sustained-release nanofiber according to claim 3, characterized in that: The propulsion speed of the spinning solution is 0.8-1.5 ml / h.

10. The method for preparing hydroxyapatite-modified drug-loaded sustained-release nanofibers according to claim 9, characterized in that: The drying conditions are as follows: temperature of 40-50° C. and time of 30-60 min.